Normal Limits of Electrocardiogram and Cut-Off Values for Left Ventricular Hypertrophy in Young Adult Nigerians (Nigerian Journal of Physiological Sciences, 2021)
Summary: This study assessed healthy young adults to determine the normal limits for electrocardiographic variables and cut-off values for left ventricular hypertrophy. It was a cross sectional descriptive study in which the participants were evaluated clinically by standard 12-lead resting electrocardiogram (ECG) at 25mm/s during quiet respiration. The heart rate, P wave duration, axis and amplitude, PR and QT intervals, QRS duration, axis and amplitude and T wave axis were assessed. Three hundred and twenty four (324) volunteers comprising of 175 males and 149 females aged 20 to 30 years (mean, 23.01±2.88years) participated in the study. The normal limits for heart rate, P wave duration, amplitude and axis in lead II, QRS duration and axis, T wave axis, PR interval, QT interval and QTc respectively were; 61-93beats per minute,0.08-0.12s,1.00-2.00mm,22.00-79.000,78.00-106.00ms,15.50-81.000, 24.25-69.000,0.12-0.19s, 0.32-0.40s and 0.36-0.44s. The cut-off values for Sokolow-Lyon, Cornell and Araoye criteria for assessment of left ventricular hypertrophy (LVH) were higher than those previously in use in medical practice. Gender difference exists in some cut-off values for LVH. This study defined the normal limits for electrocardiographic variables for young adult Nigerians. Racial factor should be taken into consideration in interpretation of ECG.